A simulator of intelligent transportation systems - Figueiredo, Lino (2019)
This paper presents the most recent developments of the Simulator of Intelligent Transportation Systems (SITS). The SITS is based on a microscopic simulation approach to reproduce real traffic conditions in an urban or non-urban network. The program provides a detailed modelling of the traffic network, distinguishing between different types of vehicles and drivers and considering a wide range of net-work geometries. In order to analyse the quality of the microscopic traffic simulator SITS a benchmark test is per-formed.